2019
DOI: 10.3390/w11051105
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Agricultural Drought Considering the Hydrological Cycle and Crop Phenology in the Korean Peninsula

Abstract: Hydrological changes attributable to global warming increase the severity and frequency of droughts, which in turn affect agriculture. Hence, we proposed the Standardized Agricultural Drought Index (SADI), which is a new drought index specialized for agriculture and crops, and evaluated current and expected droughts in the Korean Peninsula. The SADI applies crop phenology to the hydrological cycle, which is a basic element that assesses drought. The SADI of rice and maize was calculated using representative hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
(101 reference statements)
2
8
0
Order By: Relevance
“…Based on that, SPI‐3 was assumed to be representative for describing agricultural drought conditions. Previous works on agricultural drought analysis also selected SPI‐3 (i.e., Bachmair et al, ; Lim et al, ; Sigdel & Ikeda, ), supporting our decision. For example, Bachmair et al () performed a correlation analysis between SPI at different time scales and remote sensing‐based vegetation indices for Europe.…”
Section: Resultssupporting
confidence: 76%
“…Based on that, SPI‐3 was assumed to be representative for describing agricultural drought conditions. Previous works on agricultural drought analysis also selected SPI‐3 (i.e., Bachmair et al, ; Lim et al, ; Sigdel & Ikeda, ), supporting our decision. For example, Bachmair et al () performed a correlation analysis between SPI at different time scales and remote sensing‐based vegetation indices for Europe.…”
Section: Resultssupporting
confidence: 76%
“…Indeed, the temperature rise and associated increase in precipitation volatility are expected to cause significant damage to non-irrigated rice paddies. These results are remarkably similar to previous agriculture/drought cases for the same periods and areas [23], which suggests that they accurately reflect the impact of drought or disrupted water balance on productivity. In particular, the decline in productivity in the western plains is likely to be a major threat to food security.…”
Section: Assessment Of Climate Change Impact On Crop Productivitysupporting
confidence: 84%
“…Although some weather data had a coarser spatial resolution, they were given a spatial resolution of 1 km 2 to determine the spatial difference and quantification of water supply and demand. Previous research also indicated that a spatial resolution of 1 km 2 was appropriate for agriculture and forestry in studies of the Korean Peninsula [23,31].…”
Section: The Concept Of Water-centric Nexus and Spatiotemporal Settingmentioning
confidence: 98%
See 2 more Smart Citations